2021
DOI: 10.1038/s41598-021-81067-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of neuronal oscillations underlying nociceptive response in the mouse primary somatosensory cortex

Abstract: Pain is caused by tissue injury, inflammatory disease, pathogen invasion, or neuropathy. The perception of pain is attributed to the neuronal activity in the brain. However, the dynamics of neuronal activity underlying pain perception are not fully known. Herein, we examined theta-oscillation dynamics of local field potentials in the primary somatosensory cortex of a mouse model of formalin-induced pain, which usually shows a bimodal behavioral response interposed between pain-free periods. We found that forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In addition to receiving direct inputs from cortical and subcortical regions that transmit information about motor commands or outcomes, we found that the CART + EW also received projections from multifunctional regions involved in responses to pain or threat, including the somatosensory cortex (Iwamoto et al, 2021), lateral hypothalamus (Chen et al, 2020;Siemian et al, 2021), zona incerta (Chou et al, 2018;Zhou et al, 2018), and periaqueductal gray (George et al, 2019;Lefler et al, 2020) (Figure 6B).…”
Section: The Cart + Ew Is Functionally Peptidergicmentioning
confidence: 78%
“…In addition to receiving direct inputs from cortical and subcortical regions that transmit information about motor commands or outcomes, we found that the CART + EW also received projections from multifunctional regions involved in responses to pain or threat, including the somatosensory cortex (Iwamoto et al, 2021), lateral hypothalamus (Chen et al, 2020;Siemian et al, 2021), zona incerta (Chou et al, 2018;Zhou et al, 2018), and periaqueductal gray (George et al, 2019;Lefler et al, 2020) (Figure 6B).…”
Section: The Cart + Ew Is Functionally Peptidergicmentioning
confidence: 78%
“…On the other hand, Tan et al 22 reported that gamma oscillations, but not other rhythms, are specifically strengthened in the S1 cortex of mice upon noxious stimulation. Gamma oscillatory has also been linked to the pain states elicited by noxious stimuli in human subjects [78][79][80] . It is important to note that in our study, low-frequency cortical oscillations are associated with spontaneous electrical activity rather than stimulusinduced oscillatory activity as reported in other studies 22 .…”
Section: Discussionmentioning
confidence: 99%
“…First, theta oscillations could be detected in the S1 (Fig- ure 4a,b), consistent with theta-band frequency activity in the primary somatosensory cortex reported previously. [42,43] To assess the possible volume-conducted effect, [44] we rederived the local field potential (LFP) by referencing the signal against that on a neighboring electrode. [45] Theta oscillation was not abolished by LFP reference and a prominent peak at theta band could still be detected from the power spectra density (PSD) plot (Figure S13, Supporting Information).…”
Section: Weakly Theta-rhythmic Fs Hd Cellsmentioning
confidence: 99%